2023
DOI: 10.1039/d3cc03592a
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-catalyzed atroposelective synthesis of axially chiral styrenes

Pu-Fan Qian,
Tao Zhou,
Bing-Feng Shi

Abstract: Recent advances in the asymmetric synthesis of axially chiral styrenes catalyzed by transition metals were summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 190 publications
0
4
0
Order By: Relevance
“…Thus, the axially chiral alkenearenes have been much less investigated until recent years. [86][87][88][89] As a class of intermediate similar to the prominent ortho-quinone methides, Vinylidene ortho-quinone methides (VQMs) feature axial chirality due to their orthogonal π-bonds forming an allene motif. The disturbed aromaticity of the VQM led to its high Scheme 19.…”
Section: Formation Of Arylalkene Atropisomersmentioning
confidence: 99%
“…Thus, the axially chiral alkenearenes have been much less investigated until recent years. [86][87][88][89] As a class of intermediate similar to the prominent ortho-quinone methides, Vinylidene ortho-quinone methides (VQMs) feature axial chirality due to their orthogonal π-bonds forming an allene motif. The disturbed aromaticity of the VQM led to its high Scheme 19.…”
Section: Formation Of Arylalkene Atropisomersmentioning
confidence: 99%
“…Axially chiral alkenes was first mentioned and proposed by Kawabata in 1991 during the research on the memory of chirality 22 . It is only in recent years that studies for their catalytic synthesis were initiated 23 25 . Accordingly, several typical synthetic methods have been developed to date 26 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report the cobalt/organophotoredox dual-catalysis-enabled CMCA of 1,5,10-enediynes, which can be prepared from readily available 1,6-diynes, ketones, and 2-iodobenzylphosphonate (Scheme C). This reaction proceeds via the site-selective allylic C­(sp 3 )–H bond activation without the aid of DGs, affording axially chiral aryl alkenes . A combined experimental and computational mechanistic investigation revealed that the C­(sp 3 )–H bond activation at the zeta -position to the metal center of a metallole intermediate proceeds through a σ-complex assisted metathesis (σ-CAM) .…”
Section: Introductionmentioning
confidence: 99%